HW1 - momin(rrm497 – Homework 01 – cheng –(58520 1...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: momin (rrm497) – Homework 01 – cheng – (58520) 1 This print-out should have 16 questions. Multiple-choice questions may continue on the next column or page – find all choices before answering. 001 10.0 points Find all functions g such that g ′ ( x ) = 2 x 2 + 5 x + 1 √ x . 1. g ( x ) = 2 √ x ( 2 x 2 + 5 x + 1 ) + C 2. g ( x ) = 2 √ x parenleftbigg 2 5 x 2 + 5 3 x − 1 parenrightbigg + C 3. g ( x ) = 2 √ x ( 2 x 2 + 5 x − 1 ) + C 4. g ( x ) = 2 √ x parenleftbigg 2 5 x 2 + 5 3 x + 1 parenrightbigg + C cor- rect 5. g ( x ) = √ x ( 2 x 2 + 5 x + 1 ) + C 6. g ( x ) = √ x parenleftbigg 2 5 x 2 + 5 3 x + 1 parenrightbigg + C Explanation: After division g ′ ( x ) = 2 x 3 / 2 + 5 x 1 / 2 + x − 1 / 2 , so we can now find an antiderivative of each term separately. But d dx parenleftbigg ax r r parenrightbigg = ax r − 1 for all a and all r negationslash = 0. Thus 4 5 x 5 / 2 + 10 3 x 3 / 2 + 2 x 1 / 2 = 2 √ x parenleftbigg 2 5 x 2 + 5 3 x + 1 parenrightbigg is an antiderivative of g ′ . Consequently, g ( x ) = 2 √ x parenleftbigg 2 5 x 2 + 5 3 x + 1 parenrightbigg + C with C an arbitrary constant. 002 10.0 points Determine f ( t ) when f ′′ ( t ) = 4(3 t − 2) and f ′ (1) = 3 , f (1) = 1 . 1. f ( t ) = 2 t 3 + 8 t 2 − 5 t − 4 2. f ( t ) = 2 t 3 + 4 t 2 − 5 t + 0 3. f ( t ) = 6 t 3 + 8 t 2 − 5 t − 8 4. f ( t ) = 6 t 3 − 8 t 2 + 5 t − 2 5. f ( t ) = 2 t 3 − 4 t 2 + 5 t − 2 correct 6. f ( t ) = 6 t 3 − 4 t 2 + 5 t − 6 Explanation: The most general anti-derivative of f ′′ has the form f ′ ( t ) = 6 t 2 − 8 t + C where C is an arbitrary constant. But if f ′ (1) = 3, then f ′ (1) = 6 − 8 + C = 3 , i.e., C = 5 . From this it follows that f ′ ( t ) = 6 t 2 − 8 t + 5 . The most general anti-derivative of f is thus f ( t ) = 2 t 3 − 4 t 2 + 5 t + D , where D is an arbitrary constant. But if f (1) = 1, then f (1) = 2 − 4 + 5 + D = 1 , momin (rrm497) – Homework 01 – cheng – (58520) 2 i.e., D = − 2 . Consequently, f ( t ) = 2 t 3 − 4 t 2 + 5 t − 2 . 003 10.0 points Consider the following functions: ( A ) F 1 ( x ) = − cos 2 x 4 , ( B ) F 2 ( x ) = cos 2 x 2 , ( C ) F 3 ( x ) = sin 2 x 2 . Which are anti-derivatives of f ( x ) = sin x cos x ? 1. none of them 2. all of them 3. F 3 only 4. F 2 and F 3 only 5. F 1 only 6. F 2 only 7. F 1 and F 2 only 8. F 1 and F 3 only correct Explanation: By trig identities, cos 2 x = 2 cos 2 x − 1 = 1 − 2 sin 2 x , while sin 2 x = 2 sin x cos x . But d dx sin x = cos x, d dx cos x = − sin x . Consequently, by the Chain Rule, ( A ) Anti-derivative. ( B ) Not anti-derivative. ( C ) Anti-derivative. 004 10.0 points Find the value of f ( π ) when f ′ ( t ) = 4 3 cos 1 3 t − 4 sin 2 3 t and f ( π 2 ) = 2....
View Full Document

This note was uploaded on 12/11/2009 for the course M 408L taught by Professor Radin during the Fall '08 term at University of Texas.

Page1 / 9

HW1 - momin(rrm497 – Homework 01 – cheng –(58520 1...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online